Gratitude as Ecological Ethics in Islam: An Ecotheological Reading of the Nyadran Tradition in Temanggung, Indonesia - Arif Wibowo (Borneo International Journal of Islamic Studies, 2026)
Recent studies on religion and environmental sustainability have highlighted the importance of local religious traditions in fostering ecological responsibility. However, studies of the Javanese Nyadran tradition have primarily focused on its cultural and ritual dimensions, leaving its ecological and theological significance underexplored. This study examines how the Nyadran tradition in Temanggung, Indonesia, embodies ecological ethics through the Islamic concept of gratitude (shukr). Drawing on Al-Ghazali’s theory of gratitude, which integrates al-'ilm (knowledge), al-hal (spiritual disposition), and al-'amal (ethical action), this research develops an ecotheological interpretation of Nyadran and its relationship to environmental stewardship. Using a qualitative approach and cultural hermeneutic analysis, the study interprets the symbolic meanings embedded in Nyadran Kali and Nyadran Makam through observations, interviews, and local cultural narratives. The findings reveal that Nyadran functions not only as a ritual expression of gratitude to God but also as a communal mechanism for cultivating environmental awareness and responsibility. Through practices that honor water sources, agricultural landscapes, and ancestral heritage, local communities express gratitude by preserving the natural environment that sustains their livelihoods. The study argues that Nyadran operationalizes the Islamic principles of khalifah (stewardship) and amanah (trusteeship), transforming gratitude from an individual spiritual virtue into a collective ecological ethic. By demonstrating how local Islamic traditions contribute to environmental sustainability, this research advances contemporary discussions in Islamic ecotheology and offers a culturally grounded framework for faith-based ecological conservation.